Composites in infrastructure : building new markets - Marsh, Elizabeth (Elsevier, 2000)
Infrastructure is currently one of the most significant markets for composite materials and is expected to become even more significant to the composites industry as the sector increases its acceptance of fibre and carbon reinforced plastics. This new report, from the publisher of Reinforced Plastics magazine, examines the main infrastructure market sectors per region, providing market forecasts for all significant applications worldwide. For a PDF version of the report please call Tina Enright on +44 (0) 1865 843008 for price details.